Coagulation-related genes COL3A1 and MMP1 influence the development of osteoarthritis and the surrounding immunological environment - Huang, Liangkun; Wang, Xuezhong; Pei, Zijie; Zhang, Ze; Sun, Fengpo; Wen, Liangyuan (Frontiers in Immunology, 2026)
BackgroundCoagulation is an important physiological process for the body to cope with vascular injury, involving platelet activation, coagulation factor cascade reaction and fibrin formation. The role of the coagulation system in inflammatory and degenerative diseases has received increasing attention in recent years. However, its impact for osteoarthritis remains to be well investigated.MethodsThe GEO database provided us with microarray data that included osteoarthritis and normal samples. The Genecards database provided coagulation-related genes. Protein interaction network analysis, machine learning, and screening for differentially expressed genes were used to identify coagulation-related core genes relevant to osteoarthritis. Coagulation-related osteoarthritis subtypes were identified by clustering analysis. Enrichment analysis and immune infiltration analysis revealed the potential mechanism of coagulation-related genes promoting osteoarthritis progression. The screened core genes were further validated by chondrocyte experiments.ResultWe successfully screened the coagulation-related genes COL3A1 and MMP1 as core genes for osteoarthritis diagnosis. Both nomogram and diagnostic model constructed based on them have excellent diagnostic value, while OA samples can be classified into different subtypes. Immune infiltration study confirmed enrichment analysis’s finding that COL3A1 could affect the course of osteoarthritis by controlling immunological pathways. Basic research confirms that overexpression of COL3A1 inhibits proliferation and viability of chondrocytes and promotes senescence and damage. We confirmed that COL3A1 is an intervention target for osteoarthritis.ConclusionOur study identifies osteoarthritis subtypes associated with coagulation and reveals the regulatory role of COL3A1 on chondrocytes in inflammatory environment. It offers fresh perspectives on osteoarthritis management.